Inappropriate initial urinary catheter placement among older Chinese hospital inpatients: An observational study. Issue 2 (2nd December 2019) - Jiang, Wei; Song, Yunling; Zhang, Huanhuan; Huang, Rongzhong; Yin, Ying; Tan, Botao
Abstract: Aim: The aim of this study is to evaluate incidences of inappropriate initial urinary catheter placements within an older inpatient cohort. Methods: A total of 200 inpatients that received urinary catheterizations within 24 hours of admission were recruited for this observational study. The key demographic and clinical factors were recorded. Adverse outcomes were assessed by examining incidences of catheter‐associated urinary tract infection (CAUTI) during hospitalization, after transfer to skilled nursing facilities, second, duration of hospital stay and by scoring changes on the Katz Index of Independence in Activities of Daily Living. Correlative relationships between demographic data and clinical factors with adverse outcomes were analyzed. Results: Inappropriate initial urinary catheterization in our cohort was approximately 39%. This was associated with elevated Charlson comorbidity index scores and increased dependency, with correlations to medical diagnosis. We also observed that the primary rationale for the procedure (inappropriate catheterization) was for neurogenic bladder (where intermittent catheterization was indicated) and in 'convenience‐of‐care' catheterizations. Inappropriate catheter placement was ultimately associated with an elevated CAUTI at point of discharge, with transfers to skilled nursing facilities and also with an increased duration of hospital stay. Conclusions: Inappropriate catheter placement was prevalence in southwestern China and associated with adverse outcomes. SUMMARY STATEMENT: What is already known about this topic? Urinary catheterization is a common procedure for geriatric in‐patients, yet up to half of such placements are inappropriately performed. Reducing inappropriate urinary catheter use is key to minimizing adverse outcomes such as urinary tract infection and genitourinary trauma. Although guidelines for in‐patient catheterization have been developed, there are no uniform standardized national guidelines in China that could advise physicians on the placement of inpatient urinary catheters. What this paper adds? High incidences of inappropriate initial urinary catheterizations in mainland China have been reported (as represented by a hospital in southwestern China). This study finds that inappropriate catheter placements are associated with catheter‐associated UTIs at the point of discharge, with transfers to skilled nursing facilities, and an increased duration of stay. We also find that inappropriate catheter placements occur when catheterization is indicated for neurogenic bladder (with intermittent catheterization), and for 'convenience‐of‐care' purposes. The implications of this paper: The study identifies situations where older in‐patients have an elevated risk of receiving inappropriate initial urinary catheterization which should receive special attention. The findings of this study highlight the need to develop effective uniform strategies to reduce inappropriate catheterization for older Chinese patients. The factors associated with inappropriate catheterization based on our findings could be useful in establishing the proactive strategies.